OPTIMALISASI SISTIM INFORMASI MANAJEMEN RUMAH SAKIT DI RSUD LM. BAHARUDDIN KABUPATEN MUNA - Muhammad Guntur Dano; La Ode Mohammad Masri; La Ode Baka; Muhammad Suriyadarman Rianse (Journal Publicuho, 2024)
This study aims to determine the extent of the implementation of the LM Baharudin Regional General Hospital Management System in Muna Regency. This study uses a qualitative approach, with primary and secondary data sources and supporting data obtained from books, journals, and report documents related to this study. The data analysis technique uses interactive data analysis according to Miles Huberman and Saldana. The results of the study show that SIMRS supports hospital operations by managing patient registration, medical records, and administrative reporting accurately, increasing efficiency and effectiveness. This system also reduces human error and improves data integration and the quality of patient care. To maximize benefits, hospitals need to plan the development of SIMRS well, involve various parties, and provide training to staff. The implementation of SIMRS must be accompanied by evaluation, ongoing maintenance, and integration between units to ensure a smooth and accurate information flow.